Alfalfa Haylage Cost-Return Budget in South Central and Southeast Kansas - Warmann, Gerald W.; Fausett, Marvin R. (My University, 1998)
This publication contains information for a projected budget reflecting expected income and cost based on alfalfa haylage production in south central and southeast Kansas.
MF523_1998_10
Keywords: MF523; Economics; Crops; MF